Longitudinal compression of the platinum‐chromium everolimus‐eluting stent during coronary implantation: Predisposing mechanical properties, incidence, and predictors in a large patient cohort. Issue 5 (9th November 2012) - Leibundgut, Gregor; Gick, Michael; Toma, Aurel; Valina, Christian; Löffelhardt, Nikolaus; Joachim Büttner, Heinz; Neumann, Franz‐Josef
<x xml:space="preserve">Abstract</x> Objectives: To assess the longitudinal compression behavior of platinum‐chromium everolimus‐eluting stents, evaluate frequency of inadvertent longitudinal compression during percutaneous intervention, and define patient‐ and lesion‐related predictors of this complication. Background: Platinum‐chromium stents of Element family have unique design features to improve flexibility that may, however, impair longitudinal stability. Incidence of longitudinal stent compression during implantation and predictors for this complication are not well understood. Methods: Five contemporary stent platforms were longitudinally compressed in a bench test experiment, and spring constant, yield force, and ultimate strength were calculated from force‐strain curves. We also evaluated all coronary cases treated with an Element stent from January 1, 2010, to October 31, 2011, for documented longitudinal compression. We compared baseline characteristics and periprocedural data between patients with and without longitudinal stent compression and assessed predictors for this event by multiple logistic regression models. Results: Yield force and ultimate strength were significantly lower for the Element compared with all other tested stents. In 20 patients (1.4%) and 20 lesions (0.7%) from 1, 392 cases with 2, 839 atherosclerotic lesions longitudinal stent compression was reported. Ostial segments, number of stents, and the presence of a bifurcation were significant predictors (adjusted odds ratios [95% confidence intervals]: 8.33 [3.30–21.28], 1.57 [1.01–2.45], 3.57 [1.36–9.35], respectively). Conclusion: The Element stent exhibits the lowest overall longitudinal strength compared with four contemporary platforms. Longitudinal compression of the Element stent is a rare complication and occurs more frequently in ostial or bifurcation lesions and with multiple stents. © 2012 Wiley Periodicals, Inc.